External Adjustment in Oil Exporters : The Role of Fiscal Policy and the Exchange Rate - Behar, Alberto (IMF Working Papers; Working Paper ;, 2016)
After the decline in oil prices, many oil exporters face the need to improve their external balances. Special characteristics of oil exporters make the exchange rate an ineffective instrument for this purpose and give fiscal policy a sizeable role. These conclusions are supported by regression analysis of the determinants of the current account balance and of the trade balance. The results show little or no relationship with the exchange rate and, especially for the less diversified oil exporters (including the Gulf Cooperation Council), a strong relationship with the fiscal balance or government spending.